Strategi Optimasi Sistem Manajemen Risiko Pembiayaan pada Bank Jabar Banten Syariah - Adnan Sharif; Abdul Kohar Irwanto; Tubagus Nur Ahmad Maulana (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2015)
One of the success indicator for the bank into manage their financing risk is a Non Performing Financing (NPF) level. On the last three years, BJB Syariah’s NPF trend keep increased, then be required a research to find out profile and financing risk level that be faced by BJB Syariah. This research has some objective to: (1) Analyzing of financing risk level that be faced by BJB Syariah and (2) Analyzing, reviewing of management such as mitigation program for financing risk that be faced by BJB Syariah. To analyzing financing risk level has been used CreditRisk+ model, meanwhile to reviewing management and financing risk mitigation has been used internal and external analysis, SWOT analysis (Strengths, Weaknesses, Opportunities and Threats) and AHP (Analytical Hierarchy Process). The result from this research is profile and financing risk level of BJB Syariah still quite fit. This matter looks from expected loss period 2012-2014 still can be covered by reserved productive asset that has been done by BJB Syariah. Strategy that needed to be performed as follows enhancement director act to make a financing strategic policy such as financing portfolio spread for industry sectors that has fit prospect, making feasibility valuation for new debtor with more prudent and right on target also strengthen character valuation for new debtor using credit bureau until scorecard method